Antiviral prophylaxis or preemptive therapy for cytomegalovirus after liver transplantation?: A systematic review and meta-analysis - Yadav, Dipesh Kumar; Adhikari, Vishnu Prasad; Yadav, Rajesh Kumar; Singh, Alina; Huang, Xing; Zhang, Qi; Pandit, Prabesh; Ling, Qi; Liang, Tingbo (Frontiers in Immunology, 2022)
Background To conduct a meta-analysis with the aim of comparing the outcomes of antiviral prophylaxis and preemptive therapy for the prevention of cytomegalovirus (CMV) infection in liver transplant (LT) recipients. Methods We searched databases for qualified studies up until March 2022. Finally, a meta-analysis was carried out using a fixed-effect or random-effect model based on the heterogeneity. Results With a total of 1834 LT patients, the pooled incidence of CMV infection and CMV disease in the overall LT recipients using antiviral prophylaxis and preemptive therapy were 24.7% vs. 40.4% and 6.4% vs. 9.4%, respectively. Our meta-analysis exhibited a significant reduction in the incidence of CMV infection due to antiviral prophylaxis when compared to preemptive therapy in the high-risk group (OR: 6.67, 95% CI: 1.73, 25.66; p = 0.006). In contrast, there was a significant reduction in the incidence of late-onset of CMV disease in preemptive therapy compared to antiviral prophylaxis in the high-risk group (OR: 0.29, 95% CI: 0.12, 0.74; p = 0.009). However, the incidence of CMV disease, allograft rejection, graft loss, drug related adverse effects, opportunistic infections and mortality did not differ significantly between both the interventions (all p> 0.05). Conclusions We found the use of antiviral prophylaxis, compared with preemptive therapy, is superior in controlling CMV infection and prolonging the time to CMV disease in LT recipients without an increased risk of opportunistic infections, allograft rejection, graft loss, drug related adverse effects, development of drug resistance, and mortality.